2001
DOI: 10.1159/000049191
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fibrillin-1 Autoantibodies in Systemic Sclerosis Are GM and KM Allotype-Restricted

Abstract: GM and KM allotypes – genetic markers of immunoglobulin (Ig) γ and ĸ chains, respectively – have been shown to play an important role in genetic predisposition to some autoimmune diseases. To determine their role in susceptibility to systemic sclerosis (SSc; scleroderma) and in the generation of anti-fibrillin-1 antibodies, 148 SSc patients and 191 controls were typed for several GM and KM allotypes by a standard hemagglutination inhibition method. IgG and IgM antibodies to fibrillin-1 were measured by radioim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…GM f,z loci, too, have been implicated in autoimmune responses. 13,14 Thus, B cells carrying particular f,z allotypes on their Ig receptors may be more efficient in the uptake, processing, and subsequent presentation of hsp60-derived peptides to the collaborating T cells, resulting in anti-hsp60 autoantibody production. Although GM markers are constant-region determinants, they can influence immune responsiveness, normally associated with the variable-region, in several ways: direct contribution to the formation of idiotypic determinants, modulation of antibody binding affinity, linkage disequilibrium with alleles coding for the variable-region epitopes.…”
mentioning
confidence: 99%
“…GM f,z loci, too, have been implicated in autoimmune responses. 13,14 Thus, B cells carrying particular f,z allotypes on their Ig receptors may be more efficient in the uptake, processing, and subsequent presentation of hsp60-derived peptides to the collaborating T cells, resulting in anti-hsp60 autoantibody production. Although GM markers are constant-region determinants, they can influence immune responsiveness, normally associated with the variable-region, in several ways: direct contribution to the formation of idiotypic determinants, modulation of antibody binding affinity, linkage disequilibrium with alleles coding for the variable-region epitopes.…”
mentioning
confidence: 99%
“…More recent studies in humans have shown that immune responsiveness to a variety of antigens-infectious agents, vaccines, autoantigens, including some tumor-associated antigens-are associated with particular GM and KM allotypes, hereditary antigenic determinants of g and n chains, respectively (7)(8)(9)(10)(11)(12). The aim of the present investigation was to determine whether the variation in naturally occurring antibody levels to MUC1 in patients with gastric cancer is associated with these genetic markers.…”
Section: Introductionmentioning
confidence: 95%
“…Genetic variation is a further basis for study of IgG molecules in a variety of childhood diseases. (3) The role of Gm allotypes in genetic predisposition to filariasis, (2) typhoid fever, (4) SLE, (5) childhood allergy, (6) and systemic sclerosis (sclerodema) (7) has already been reported. In scleroderma, anti-fibrillin-1 autoantibodies are Gm and Km (allotypic markers of kappa light chains) allotype restricted.…”
Section: Introductionmentioning
confidence: 99%